From energy security to security of energy eervices: The role of gendered innovations in living labs - Batinge, B.; Musango, J.K.; Ceschin, F.; Ambole, A.; Smit, S.; Mukama, M.; Petrulaityte, A. (South African Journal of Industrial Engineering, 2022)
Energy security remains a concern in Sub-Saharan Africa. The conceptualisation of energy security at the urban household level has shifted from the security of energy supply to the security of energy services, which is focused more on the demand side. Women and young girls are affected the most by insecure energy services. However, energy policy discourses often fail to focus on the security of energy services or to recognise gender roles in the provision of energy services at the household level. It is therefore imperative to develop innovative and gender-sensitive energy services solutions with a new paradigm of participatory solution design, such as living labs. We assessed living labs and the energy security landscape in poor urban environments through a systematic literature review, and proposed a framework for demonstrating how living labs could be used as a lever to promote the security of energy services. The security of energy services in poor urban households could be improved by harnessing the different innovative strengths of the respective genders. Living labs provide an ideal space for co-generating, co-designing, and co-learning to produce tailored energy services solutions. There is a need for a collaborative effort in resourcing researchers to undertake practical investigations of interactive multi-stakeholder platforms with those who are intended to benefit from the policy to increase its impact and to bridge the science-policy divide. © 2022, South African Institute of Industrial Engineering. All rights reserved.
Keywords: accès à l'électricité; afrique; afrique subsaharienne; approches et analyses; droits des femmes*; environnement; inégalités; patriarcat; projet charge mentale; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Un projet participatif sur la réduction de la pollution atmosphérique dans quatre pays de l’Afrique de l’Ouest : quel rôle pour les femmes ? - Saint-Charles, Johanne; Yates, Stéphanie; Kêdoté, Nonvignon Marius (Recherches participatives et équité en santé, 2022)
C echapitreportesurlesdéfisd’uneapprocheparticipativeintégrant une perspective d’équité de genre rencontrés dans le cadre d’un programme de recherche-intervention sur la pollution urbaine en Afrique de l’Ouest, programme intitulé « Chaire écosanté sur la pollution urbaine de l’air et les maladies respiratoires1 ». Conçu et dirigé par des chercheurs et chercheuses de quatre pays africains (Bénin, Burkina Faso, Côte d’Ivoire et Sénégal), ce programme regroupait des équipes derecherchedechacundespays(équipes-pays)etquelquescollèguesde«paysdunord»,dontleCanada(Québec).IlaétéfinancéparleCentre de recherches pour le développement international du Canada. Outre des objectifs de recherche et de formation, la Chaire comportait un volet nommé Air-Sain qui visait à sensibiliser les actrices et acteurs dediversmilieuxetàsoutenirdeschangementsdurablesafinderéduirela pollution urbaine.
Keywords: 2000 à aujourd'hui; afrique; afrique de l'ouest; approches et analyses; droits des femmes*; environnement; inégalités; patriarcat; projet charge mentale; périodes historiques; recherche participative; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques

Nous sommes tous des féministes - Adichie, Chimamanda Ngozi (Gallimard, 2020)
Dans le premier texte, à l'origine un discours prononcé en 2012 dans le cadre d'un programme dédié à l'essor du continent africain, l'écrivaine nigériane aborde avec lucidité et humour le sujet du féminisme. A travers des anecdotes issues de sa vie quotidienne, au Nigeria comme aux Etats-Unis, elle évoque les questions de l'inégalité des sexes et de l'image de soi des femmes.
Keywords: afrique; afro-féminisme; amériques; approches et analyses; cours; cycles supérieurs; droits des femmes*; fem7000; féminismes noirs; inégalités; lit3220; nigeria; premier cycle; rapports sociaux de sexe; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; états-unis

A gendered human rights analysis of Ebola and Zika: Locating gender in global health emergencies - Davies, Sara E.; Bennett, Belinda (International Affairs, 2016)
Globally gender remains a key factor in differing health outcomes for men and women. This article analyses the particular relevance of gender for debates about global health and the role for international human rights law in supporting improved health outcomes during public health emergencies. Looking specifically at the recent Ebola and Zika outbreaks, what we find particularly troubling in both cases is the paucity of engagement with human rights language and the diverse backgrounds of women in these locations of crisis, when women-specific advice was being issued. We find the lessons that should have been learnt from the Ebola experience have not been applied in the Zika outbreak and there remains a disconnect between the international public health advice being issued and the experience of pervasive structural gender inequalities among those experiencing the crises. In both cases we find that responses at the outbreak of the crisis presume that women have economic, social or regulatory options to exercise the autonomy contained in international advice. The problem in the case of both Ebola and Zika has been that leaving structural gender inequalities out of the crisis response has further compounded those inequalities. The article argues for a contextual human rights analysis that takes into account gender as a social and economic determinant of health.
https://academic.oup.com/ia/article/92/5/1041/2688120
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; amérique latine; amériques; approches et analyses; care; droits des femmes*; inégalités; périodes historiques; ressource en ligne; régions géographiques; santé; santé publique; systèmes d'oppressions; thématiques

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs – qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those – the vast majority – who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe